The influence of integrated reporting on competitiveness of enterprises - Vaysilova, Emiliya (Leadership, Society, Strategic Visions, 2021)
In today’s globalized world, the world economy is booming. Human needs are being met more and more and the role of companies in society is growing, which unfortunately is accompanied by negative effects on the environment. In order for this role to be properly assessed, it is necessary to improve the reporting of the companies. As a result, the paradigm regarding the reporting of economic activities is changing. Integrated reporting is introduced, which includes both fi nancial and non-fi nancial indicators (social and environmental).This paper aims to explore the essence and importance of integrated reporting as one of the conditions for sustainable growth and development of enterprises. The main thesis is that, at the present stage of economic development, the presentation of non-fi nancial information is one of the main factors for enhancing the competitiveness of each enterprise.